Aspects of aristocracy : grandeur and decline in modern Britain - Cannadine, David, 1950- (Yale University Press, 1994)
In this stylish and provocative book, the eminent historian David Cannadine brings his characteristic wit and acumen to bear on the British aristocracy, probing behind the legendary escapades and indulgences of aristocrats such as Lord Curzon, the Hon. C.S. Rolls (of Rolls Royce), Winston Churchill, Harold Nicolson, and Vita Sackville-West, and changing our perceptions of them - transforming wastrels into heroes and the self-satisfied into the second-rate. Cannadine begins by investigating the land-owning classes as a whole during the last two hundred years, describing their origins, their habits, their increasing debts, and their involvement with the steam train, the horseless carriage, and the aeroplane. He next focuses on patricians he finds particularly fascinating: Lord Curzon, an unrivalled ceremonial impresario and inventor of traditions; Lord Strickland, part English landowner and part Mediterranean nobleman, who was both an imperial proconsul and prime minister of Malta; and Winston Churchill, whom Cannadine sees as an aristocratic adventurer, a man who was burdened by, more than he benefitted from, his family connections and patrician attitudes. Cannadine then moves from individuals to aristocratic dynasties. He reconstructs the extraordinary financial history of the dukes of Devonshire, narrates the story of the Cozens-Hardys, a Norfolk family who played a remarkably varied part in the life of their county, and offers a controversial reappraisal of the forebears, lives, work, and personalities of Harold Nicolson and Vita Sackville-West - a portrait, notes Cannadine, of more than a marriage. Written with sympathy and irony, devoid of snobbery or nostalgia, and handsomely illustrated, Cannadine's book is sure both to enlighten and delight.